Increases in Doublecortin Immunoreactivity in the Dentate Gyrus following Extinction of Heroin-Seeking Behavior - Megan P. Hicks; Kelly C. Wischerath; Amber L. Lacrosse; M. Foster Olive (Neural Plasticity)
Adult-generated neurons in the dentate gyrus (DG) of the hippocampus play a role in various forms of learning and memory. However, adult born neurons in the DG, while still at an immature stage, exhibit unique electrophysiological properties and are also functionally implicated in learning and memory processes. We investigated the effects of extinction of drug-seeking behavior on the formation of immature neurons in the DG as assessed by quantification of doublecortin (DCX) immunoreactivity. Rats were allowed to self-administer heroin (0.03 mg/kg/infusion) for 12 days and then subjected either to 10 days of extinction training or forced abstinence. We also examined extinction responding patterns following heroin self-administration in glial fibrillary acidic protein thymidine kinase (GFAP-tk) transgenic mice, which have been previously demonstrated to show reduced formation of immature and mature neurons in the DG following treatment with ganciclovir (GCV). We found that extinction training increased DCX immunoreactivity in the dorsal DG as compared with animals undergoing forced abstinence, and that GCV-treated GFAP-tk mice displayed impaired extinction learning as compared to saline-treated mice. Our results suggest that extinction of drug-seeking behavior increases the formation of immature neurons in the DG and that these neurons may play a functional role in extinction learning.